2023
DOI: 10.1038/s41598-023-28650-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations between oral health status and risk of fractures in elder adults

Abstract: Oral health condition, bone mineral density, skeletal muscle mass, fall, fracture, and frailty seem to be strongly interconnected. This study aimed to investigate associations between probability of osteoporotic fractures and oral health in the elderly. In total, 2322 Korean subjects from the 2008—2009 Korea National Health and Nutritional Examination Survey aged over 65 years were included. The 10-year probabilities of major and hip fractures were calculated using the Fracture Risk Assessment (FRAX) tool. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The findings indicate that oral frailty has a direct impact on the fall risk of the elderly and also indirectly affects it through nutrition. Previous studies [49][50][51] have mainly focused on the relationship between oral frailty, nutrition, and fall risk individually. This study contributes to the existing research by conducting a mediation analysis to explore the relationship between oral frailty, nutrition, and fall risk.…”
Section: Discussionmentioning
confidence: 99%
“…The findings indicate that oral frailty has a direct impact on the fall risk of the elderly and also indirectly affects it through nutrition. Previous studies [49][50][51] have mainly focused on the relationship between oral frailty, nutrition, and fall risk individually. This study contributes to the existing research by conducting a mediation analysis to explore the relationship between oral frailty, nutrition, and fall risk.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study in Korean older adults did not find a significant association between periodontal diseases and osteoporotic fracture risk. The authors indicated that the nature of the index used to evaluate periodontitis, which is affected by the number of teeth present, may have contributed to the lack of association [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal examination was performed using a method modi ed from the Community Periodontal Index, based on the criteria given by the WHO [9] , which includes bleeding on probing and pocket depth. Additionally, the number of remaining teeth, oral health conditions (dental plaque and tongue coating status on visual examination [10] ), and organoleptic malodors [11] were also measured.…”
Section: Oral Examinationmentioning
confidence: 99%